A micromanipulation system for single nanostructure material deposition using resistance. Issue 172 (12th June 2016) - Xu, Ke; Qi, Yuanwei; Gao, Zhijun; Wang, Li; Gong, Wei; Liu, Xiyang; Li, Hongwei; Wang, Xing; Mao, Yongming
ABSTRACT: An automation operation system for the single cell aspiration and placement with high throughput were presented in this article. In the system, the control system was firstly utilized to move the micropipette to the place above the microwell which contained the cell, and measure the current distance between the top of the micropipette and the bottom of the microwell device in advance by atomic force microscopy. Then we can move the micropipette to the cell of interested region by the computer to control the motor and aspire and transfer it to the target microwell for placement according to the record in the computer about the position relation between the micropipette and the target microwell. In the process, we built a system of the resistance–based voltage feedback, with which we could judge the whether the cell was aspired or placed. The target of the paper was to realize the automated operation of the cell in the microwell array that contains the aspiration, transfer and placement with high efficiency.